Cross-sectional analysis of triglycerides and serum uric acid association in ovarian cancer patients - Zhang, Shuqi; Li, Peiyao; Xu, Haifeng; Zhao, Xiaoli; Xiao, Han; Li, Wenjuan; Li, Ping; Chen, Fang; Zhu, Lixia (Frontiers in Oncology, 2026)
BackgroundAlthough numerous studies have investigated the association between triglycerides (TG) and serum uric acid (SUA) in various populations, this association has not yet been explored in patients with ovarian cancer (OC). This article aims to examine the association between TG and SUA specifically in OC patients.MethodsThis was a retrospective cross-sectional examination of data from 724 OC patients sourced from the Affiliated Kunshan Hospital of Jiangsu University database, hospitalized between December 2014 and May 2025. The baseline TG served as the exposure variable, whereas SUA levels constituted the study outcome. When analyzing this association, adjustments were made for age, various baseline clinical and laboratory parameters, followed by the fitting of separate univariate and multivariate linear regression models. This association was further characterized through smooth curve fitting, multiple regression equations, and threshold effect analyses.ResultsA non-linear association between TG and SUA levels was discerned and modeled using a piecewise linear regression with an inflection point at 2.82 mmol/L. The analysis using piecewise multivariate linear methods indicated a substantial positive association between TG and SUA at TG levels below 2.82 mmol/L (β =52.73, 95% CI: 41.99 to 63.74, P < 0.01).ConclusionsThis article reveals a non-linear association between TG and SUA, identifying a potential threshold effect. These findings offer new insights into their association in OC patients. However, given the cross-sectional design, these results represent associative rather than causal relationship and should be considered hypothesis-generating for future prospective studies.